Context-based Ontology Matching: Concept and Application Cases - Feiyu Lin; Butters, J; Sandkuhl, K; Ciravegna, F (2010 IEEE 10th International Conference on Computer and Information Technology, 2012)
Work presented in this paper addresses the challenge of bringing together concepts and experiences from two different areas of computer science: context modeling and ontology matching. Current work in the field of automatic ontology matching does not take into account the context of the user during the matching process. This paper is organized as follows, (1) we introduce of the concept of "context" in the ontology matching process, (2) we introduce the use cases and motivation along with an example of the use of context and (3) an approach for context-based semantic matching, which builds on different (weighted) levels of overlap for a better ranking of alignment elements depending on user's demand.